On the Concept of Good with Continual Reference to Economy. What is the axiological background of collaborative consumption society? - Nowak, Karolina (Research Papers in Economics and Finance, 2022)
The rationale for choosing the object of research is the recognition of the socio-cultural validity of new ways of management (New Economy), interpreted as a response to the exhaustion of traditional ways in which societies function, i.e. those based on ideas of growth and ownership. The aim of the article is to analyse selected examples of redefinition of the concept of good in the context of new social narratives and the grounding of certain beliefs related to the idea of degrowth and sharing economy. The article is theoretical and references to contemporary research on cultural philosophy and social analyses of economic practice. A socio-regulatory concept of culture was adopted as a research perspective, and humanistic interpretation was used as an explanatory procedure. Qualitative data was analysed using atlas.ti, concept driven coding was used, and content analysis was limited to concept analysis and the creation of conceptual maps. The research results are supposed to show: 1. the impact of modern forms of economic practices using the Internet and IT technology on the redefinition of good, 2. how this redefinition builds the axiological background of society of collaborative consumption.